ANALYSIS CURRICULUM POLICY MODEL AT MAN 1 LABUHANBATU DURING THE COVID-19 PANDEMIC - Jailani Syahputra Siregar; Rahmat Hidayat Rambe; Syaparuddin Siahaan; Makmur Syukri (SEAN Institute, 2022)
The Covid-19 that entered unexpectedly and became an epidemic resulted in a transformation in the field of education. Educational activities have changed. Government regulations to break the chain of the spread of Covid-19 require learning to be done from home. One of the important innovations is the implementation of the curriculum. The curriculum is an important component in the educational journey. Facing the Covid-19 situation, there must be innovation in the existing curriculum. This study aims to analyze the Curriculum Policy Model at MAN 1 Labuhanbatu during the Covid-19 pandemic. To see how MAN 1 Labuhanbatu runs the curriculum in non-routine situations. To see how the management of MAN 1 Labuhanbatu in implementing the existing curriculum. To see how educators run the existing curriculum. To see how students undergo learning based on the existing curriculum when learning from home is implemented. This type of research is qualitative research. The study used a semi-structured interview method, namely in-depth interviews with informants. Curriculum policy at MAN 1 Labuhanbatu during the Covid-19 pandemic is in the good category. Learning planning refers to and adapts to the learning situation at home, guided by the MAN 1 Labuhanbatu Curriculum. In the implementation section, teachers utilize technology-based facilities and application facilities to facilitate the delivery of goals and teaching materials. Assessment and evaluation are still carried out objectively.